Energy Efficient Radio Resource Allocation in Two-Tier Macro-Femto Cellular for Mobile Cloud Computing - Guogang Zhao; Liqiang Zhao; Kun Yang (Dianxin kexue)
Two-tier macro-femto-cellular networks have initially been proposed as a solution to the poor indoor coverage problem, but they are also capable of substantially reducing the overall energy consumption. However, the cross-tier and co-tier interference have to be carefully controlled with the aid of specific radio resource allocation and optimization techniques. A mobile cloud computing management architecture was proposed firstly. Then novel concept of spatial transmission efficiency for PtP radio link was first introduced with several existing efficiency metrics compared. An analytical model was conceived and a radio resource management algorithm based on LTE-A mobile cloud computing was designed. In order to achieve the optimal solution quickly, a rapid convergence of the iterative algorithm was designed. Simulation result shows the proposed algorithm achieves the maximum of system energy efficiency with a superior tradeoff with system throughput.